PPARα-Independent Arterial Smooth Muscle Relaxant Effects of PPARα Agonists - Neerupma Silswal; Nikhil K. Parelkar; Michael J. Wacker; Mostafa Badr; Jon Andresen (PPAR Research)
We sought to determine direct vascular effects of peroxisome proliferator-activated receptor alpha (PPARα) agonists using isolated mouse aortas and middle cerebral arteries (MCAs). The PPARα agonists GW7647, WY14643, and gemfibrozil acutely relaxed aortas held under isometric tension and dilated pressurized MCAs with the following order of potency: GW7647≫WY14643>gemfibrozil. Responses were endothelium-independent, and the use of PPARα deficient mice demonstrated that responses were also PPARα-independent. Pretreating arteries with high extracellular K+ attenuated PPARα agonist-mediated relaxations in the aorta, but not in the MCA. In the aorta, the ATP sensitive potassium (KATP) channel blocker glibenclamide also impaired relaxations whereas the other K+ channel inhibitors, 4-aminopyridine and Iberiotoxin, had no effect. In aortas, GW7647 and WY14643 elevated cGMP levels by stimulating soluble guanylyl cyclase (sGC), and inhibition of sGC with ODQ blunted relaxations to PPARα agonists. In the MCA, dilations were inhibited by the protein kinase C (PKC) activator, phorbol 12,13-dibutyrate, and also by ODQ. Our results demonstrated acute, nonreceptor-mediated relaxant effects of PPARα agonists on smooth muscle of mouse arteries. Responses to PPARα agonists in the aorta involved KATP channels and sGC, whereas in the MCA the PKC and sGC pathways also appeared to contribute to the response.